Microbial bioconversion of palm oil mill effluent to citric acid with optimum process conditions - Jamal, Parveen (Springer Science, 2007)
Oil palm industry has an important role in contributing to the Malaysian economy. Several million tonnes of crude palm oil is produced annually and approximately, about 10 million tonnes of palm oil mill effluent (POME) (highly polluted organic effluent) is generated every year. Citric acid is a commercially valuable product widely used in many industries. More than 400,000 tonnes of citric acid is produced annually by fermentation of expensive raw materials like glucose and sucrose. Efficient and effective methods of producing citric acid from different cheaper raw materials have been of great interest to many researchers, due to its extensive use. This study is an effort to achieve the goal by introducing a new substrate POME and a potential isolated strain of Asperillus niger. The method used was liquid state bioconversion with optimum process conditions obtained from our previous studies using central composite design (CCD)from Minitab software. The optimized parameters were temperature, agitation rate, inoculum size and pH. Analysis has been done everyday up to seven days of fermentation. Performance of the developed process was evaluated on the basis of maximum citric acid (5.24 g/L), chemical oxygen demand removal (COD), total suspended solid (TSS) and removal of heavy metals (cadmium chromium and copper).